2003
DOI: 10.1161/01.res.0000076892.18394.b6
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Stunning Induces Myocardial Hibernation and Protection

Abstract: Abstract-To test the hypothesis that persistent myocardial stunning can lead to hibernating myocardium, 13 pigs were chronically instrumented, and persistent stunning was induced regionally by 6 repetitive episodes of 90-minute coronary stenosis (CS) (30% reduction in baseline coronary blood flow [CBF]) followed by full reperfusion every 12 hours. During the 1st CS, CBF fell from 43Ϯ2 to 31Ϯ2 mL/min, and anterior wall thickening (AWT) fell by 54Ϯ8%, but posterior WT did not change. AWT never recovered fully an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 46 publications
3
90
0
3
Order By: Relevance
“…2), i.e., all of these models reduce infarct size during a subsequent lethal ischemic stimulus by at least 60%. 18 In addition, the repetitive ischemia model results in a prolonged state of chronic myocardial stunning, 19,20 i.e., depressed cardiac function without reduced myocardial blood flow, resembling "hibernating myocardium" in patients with chronic coronary artery disease. 21 We have previously reported that the repetitive ischemia model elicits cardioprotection, in part, by inducing autophagy.…”
Section: Autophagy In Ischemic Preconditioningmentioning
confidence: 99%
“…2), i.e., all of these models reduce infarct size during a subsequent lethal ischemic stimulus by at least 60%. 18 In addition, the repetitive ischemia model results in a prolonged state of chronic myocardial stunning, 19,20 i.e., depressed cardiac function without reduced myocardial blood flow, resembling "hibernating myocardium" in patients with chronic coronary artery disease. 21 We have previously reported that the repetitive ischemia model elicits cardioprotection, in part, by inducing autophagy.…”
Section: Autophagy In Ischemic Preconditioningmentioning
confidence: 99%
“…Subsequently, myocardium exposed to repeated ischemia is adapted to chronic ischemia. This adaptation is called hibernation, where the main energy substrate shift from LCA to glucose, contractility is impaired, and MFR is severely reduced [9,11,13,14]. Our study possibly suggests that the substrate shift in hibernation.…”
Section: Resultsmentioning
confidence: 69%
“…As a result, CPT-1 and FAO are inhibited and LCFA metabolism is suppressed. In fact, basic research suggested that repetitive ischemia caused the substrate shift from LCFA to glucose [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An experimental study has found that 123 I-BMIPP uptake in the ischemic territories recovers within 30 days. 29) Consequently, in a case of repeated coronary spasm, 30) 123 I-BMIPP imaging cannot distinguish recent spontaneous ischemia from ischemic episodes induced by provocation. Although we could not clarify the relationship between 123 I-BMIPP myocardial defects and the length of luminal narrowing due to coronary vasospasms, we speculate that the severity of a luminal narrowing as well as a diffuse spastic lesion may have a significant myocardial ischemia.…”
Section: I-bmipp Findingsmentioning
confidence: 99%